Model Digital Needs Assessment Program of Community Empowerment - Purnomo, Achmad Hufad, Uyu Wahyudin, Ade Sadikin Akhyadi, Nani Sutarni, Abdul Rahmat (International Journal of Control and Automation, 2020)
The model needs assessment developed is the development of an information and communication technology (ICT) approach as a strategy in determining the needs of effective community empowerment programs in accordance with the abilities of KB family cadres, the majority of whom are aged 40 years and over. This study uses a research and development approach, with data collection techniques of observation, interviews, and group discussions. It is expected that the model needs assessment can improve the competence of KB Village cadres in designing community empowerment programs with the principles of collaborative, participatory, relevance, efficiency and effectiveness. Implementation models digital needs assessment for program empowerment will take place on an ongoing basis, and is not completed or stopped on the implementation of the specific activities, guided to continue to discuss other issues of her.